Behavioral Effects of Continuously Administered Bergamot Essential Oil on Mice With Partial Sciatic Nerve Ligation - Hamamura, Kengo; Katsuyama, Soh; Komatsu, Takaaki; Scuteri, Damiana; Bagetta, Giacinto; Aritake, Kosuke; Sakurada, Tsukasa (Frontiers in Pharmacology, 2020)
Neuropathic pain is an intractable chronic pain condition that is mainly caused by allodynia. We had previously reported that intra-plantar administration of bergamot essential oil (BEO) containing an aromatic compound significantly suppressed partial sciatic nerve ligation (PSNL)-induced mechanical allodynia via opioid mu receptors in mice. However, it has also been reported that the inhalation of BEO reduced formalin-induced nociceptive responses. Therefore, we aimed to elucidate whether the analgesic action of BEO is mediated by olfactory stimulation through volatile components. In the current study, BEO was continuously administered with an osmotic pump during PSNL surgery, and the effects on mice behavior were examined pharmacologically using a double activity monitoring system, which can detect two-dimensional planar motion in a cage with an infrared beam sensor as well as active motion with a running wheel. Here, we report that the two-dimensional planar activity significantly increased in mice with PSNL in the light phase (from 8 o’clock to 20 o’clock) but not in the dark phase (from 20 o’clock to 8 o’clock) from the second day after surgery. However, this increase was not observed when BEO was continuously administered. The effect of BEO on the two-dimensional planar counts in mice with PSNL was antagonized by naloxone hydrochloride. Regarding the running wheel activity, the number of rotations decreased by PSNL in the dark phase from the 8th day after surgery. However, this was not apparent with BEO use. The effect of BEO on the number of rotations was also antagonized by naloxone hydrochloride. Furthermore, inhalation of BEO in PSNL mice did not affect mechanical allodynia or the two-dimensional planar motion or running wheel activities. These findings indicate that BEO exhibits an analgesic action, which is mediated by opioid receptors and not by the olfactory system.